2018
DOI: 10.1186/s10194-018-0901-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of clinical improvement after greater occipital nerve (GON) block in chronic migraine: relevance for chronic migraine pathophysiology

Abstract: BackgroundTherapeutic management of Chronic Migraine (CM), often associated with Medication Overuse Headache (MOH), is chiefly empirical, as no biomarker predicting or correlating with clinical efficacy is available to address therapeutic choices. The present study searched for neurophysiological correlates of Greater Occipital Nerve Block (GON-B) effects in CM.MethodsWe recruited 17 CM women, of whom 12 with MOH, and 19 healthy volunteers (HV). Patients had no preventive treatment since at least 3 months. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
(53 reference statements)
0
23
0
1
Order By: Relevance
“…The number of attacks is the main risk factor for chronification itself (Buchgreitz et al, 2006). In CM, outside an attack, the neurophysiological response to repeated stimuli is similar to the pattern found in episodic form during an attack: hyperexcitability, central sensitization and normal habituation (Ayzenberg et al, 2006; Chen et al, 2011, 2012; Mathew, 2011; Schoenen, 2011; Viganò et al, 2018). Interestingly, when patients are successfully treated and return to episodic migraine, the low preactivation and the lacking habituation reappear (Chen et al, 2011, 2012).…”
Section: Neural Plasticity and Its Relationship To Chronic Migrainementioning
confidence: 53%
See 2 more Smart Citations
“…The number of attacks is the main risk factor for chronification itself (Buchgreitz et al, 2006). In CM, outside an attack, the neurophysiological response to repeated stimuli is similar to the pattern found in episodic form during an attack: hyperexcitability, central sensitization and normal habituation (Ayzenberg et al, 2006; Chen et al, 2011, 2012; Mathew, 2011; Schoenen, 2011; Viganò et al, 2018). Interestingly, when patients are successfully treated and return to episodic migraine, the low preactivation and the lacking habituation reappear (Chen et al, 2011, 2012).…”
Section: Neural Plasticity and Its Relationship To Chronic Migrainementioning
confidence: 53%
“…As neurotransmitter, serotonin seems to be directly involved. In a recent paper of our group, we investigated electrophysiological patterns associated to transition from CM to EM after GON anesthetic block (Viganò et al, 2018). We found that during the recovery from chronic to episodic migraine, an early increase of the serotonin firing (within the 1st week after GON block) was found in patients who had clinical improvement in the following weeks.…”
Section: Neural Plasticity and Its Relationship To Chronic Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…Not many trials have been conducted to investigate the efficacy of cephalic segment peripheral nerve blocks in the management of chronic migraine. The heterogeneity of study cohorts, designs and techniques do not allow consistent conclusions 111,112,113,114 . However, it is worth mentioning a doubleblind RCT in which 44 participants were submitted to weekly bilateral greater occipital nerve blockades for one month, with 0.5% bupivacaine or saline solution (1.5 mL).…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%
“…A recent neurophysiological study investigating the serotonergic tone, found a low baseline serotonergic tone in chronic migraineurs with MOH, but it recovers after a week following anaesthetic block of the greater occipital nerve. Moreover, the size of the recover positively correlated with the clinical benefit after a month [103].…”
Section: Medication Overuse Headachementioning
confidence: 85%